Quantitative lean assessment of line of balance schedules' quality. Issue 2 (26th March 2019) - Ungureanu, Lucian Constantin; Hartmann, Timo; Serbanoiu, Ion
Abstract : Purpose: The line of balance (LOB) method is a suitable scheduling technique that managers can use to support lean planning efforts for projects composed of repetitive activities such as high-rise building construction. Like any other method, LOB has certain disadvantages that create a set of practical limitations in its application. An LOB schedule gives insights about how continuous and synchronized single resources are scheduled and how uniform these resources are distributed over the project duration. However, these three characteristics have to be visually checked, which makes the evaluation and the comparison of different schedule alternatives difficult. To overcome this problem, the purpose of this paper is to present a quantitative method to calculate quality degrees for the continuity, the synchronization and the uniformity of an LOB schedule that can be applied to assess an LOB schedule globally. Design/methodology/approach: The paper introduces a set of global indicators, termed quality degrees, which allow for a quick quantitative evaluation of LOB schedules at the global level. These quality degrees are quantitative indicators for the: degree of continuity, degree of synchronization and degree of uniformity within a specific LOB alternative. A mathematical model was developed to calculate the quality degrees for LOB schedules. This model was validated using a well-known case study extracted from literature, and its practical implementation was exemplified on two real Romanian projects. Findings: The paper illustrates this contribution using two case studies that confirm that the proposed method can be used to evaluate different schedule alternatives. In particular, the paper shows that quality indicators can be used to analyze and control interdependencies between cost and time. Research limitations/implications: The main limitation of the proposed method is that it cannot indicate the desired level of continuity, synchronization or uniformity to be achieved. Further studies need to explore this possibility, as well the relationship between indicators. Practical implications: The presented quality indicators contribute to existing LOB methods as they allow for the quick analysis and assessment of schedules without an in-depth visual analysis. Originality/value: The paper proposes an innovative method, mathematically formulated, to quantitatively assess the quality aspects of continuity, synchronization and uniformity for LOB schedules.